Effect of a single dose of preoperative gabapentin in oncourology on the intensity of early postoperative pain - Lisnyy, I I; Klimchuk, L V (Pain medicine, 2021)
Objective: to evaluate the intensity of early postoperative pain after a single preoperative administration of gabapentin during surgical interventions in oncourology. Materials and methods: patients were randomized into two groups of 25 people each: group 1 (Gr. 1) received gabapentin at a dose of 300 mg for premedication at night, and group 2 (Gr. 2), in which patients did not receive gabapentin. The need for propofol during anesthesia, the need for fentanyl during anesthesia, and the intensity of pain at 2, 4, 6, 12 and 24 hours after surgery were assessed on the VAS scale at rest and during movement. Results of the study: it was shown that in patients who received gabapentin at a dose of 300 mg for premedication, the need for propofol and fentanyl was significantly lower when compared with patients who did not receive gabapentin, p = 0.0001. The intensity of postoperative pain syndrome in patients in Gr. 1 was significantly lower only when assessed at rest, while no statistically significant differences were found in the quality of pain relief during movement. Conclusions: the use of gabapentin at a dose of 300 mg for premedication significantly reduces the intensity of postoperative pain at rest, but not during movement, and also reduces the need for propofol and fentanyl during surgery.